2022
DOI: 10.1007/s00442-022-05199-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant richness, land use and temperature differently shape invertebrate leaf-chewing herbivory on plant functional groups

Abstract: Higher temperatures can increase metabolic rates and carbon demands of invertebrate herbivores, which may shift leaf-chewing herbivory among plant functional groups differing in C:N (carbon:nitrogen) ratios. Biotic factors influencing herbivore species richness may modulate these temperature effects. Yet, systematic studies comparing leaf-chewing herbivory among plant functional groups in different habitats and landscapes along temperature gradients are lacking. This study was conducted on 80 plots covering la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
3
3
0
Order By: Relevance
“…Average herbivory was three times higher in forb species compared to grasses, most likely caused by higher palatability and lower physical resistance of forbs compared to grasses (Lavorel and Garnier 2002 ; Firn et al 2019 ). Similar ratios were found by others (Turcotte et al 2014 ; Fricke et al 2022 ). Furthermore, plant traits explained differences among grasses, but not among forbs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Average herbivory was three times higher in forb species compared to grasses, most likely caused by higher palatability and lower physical resistance of forbs compared to grasses (Lavorel and Garnier 2002 ; Firn et al 2019 ). Similar ratios were found by others (Turcotte et al 2014 ; Fricke et al 2022 ). Furthermore, plant traits explained differences among grasses, but not among forbs.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed variation in herbivory and mixed results for diversity effects on herbivory (Scherber et al 2006 ; Schuldt et al 2010 ; Vockenhuber et al 2013 ; Loranger et al 2014 ; Hahn et al 2017 ; Fricke et al 2022 ). Here, we studied species-specific herbivory in one of the largest grassland biodiversity experiments (Jena Experiment) and found that the average herbivory strongly differed among plant species and functional groups (forbs species were more damaged by herbivores than grasses).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While in general fungal pathogens are more common on grasses and insect herbivores are more common on forbs (Ebeling et al, 2022;Fricke et al, 2022), a pattern also borne out in our experiment (Fig. S8), it appears that both forbs and C4 grasses can benefit from release of insect herbivory during recruitment.…”
Section: 1enemy Release Increases Early Survival and Recruitment Of C...supporting
confidence: 73%
“…However, this previous work focused on biomass rather than early survival, again emphasising the importance of considering different exotic life-history stages. While in general fungal pathogens are more common on grasses and insect herbivores are more common on forbs (Ebeling et al ., 2022; Fricke et al ., 2022), a pattern also borne out in our experiment (Fig. S8), it appears that both forbs and C4 grasses can benefit from release of insect herbivory during recruitment.…”
Section: Discussionmentioning
confidence: 99%